Load Balancing Techniques in Cloud Computing - Neha Bhosale; Tejashri Shinde; Shantanu Nimbalkar (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
A robust concept of cloud computing enables individuals and businesses to get the necessary services in accordance with their environment requirement. The model offers an array of functionalities which contain storage, deployment platform, easy to access resources on web. In the cloud, load balancing a frequent complication that makes it difficult to maintain performance with respect to service level Agreement (SLA) and be close to qualitity of Service (QOS)measurement contract as needed by the cloud service providers to organizations. To distribute a similar workload distribution across servers is a obstacle for cloud service providers. To solve this issue, a concept known as load balancing strategies that improve network management conformance was recently put out. Due to needs fulfilment and resource restrictions on the network, load balancing becomes essential in order to distribute traffic across available resources more effectively and reliably.